Case Report: First Evidence of a Benign Bone Cyst in an Adult Teckel Dog Treated With Shark Teeth-Derived Bioapatites - García-González, Mario; Muñoz Guzón, Fernando María; González-Cantalapiedra, Antonio; López-Peña, Mónica; de Frutos Pachón, Felipe; Pereira-Espinel Plata, Teresa; González Fernández, Pío Manuel; Serra Rodríguez, Julia Asunción (Frontiers in Veterinary Science, 2021)
Bone cysts are a very rare orthopaedic pathology in veterinary medicine, which general prevalence is unknown. An unicameral bone cyst was diagnosed in an adult female Teckel dog with a limp and was treated surgically filling the defect with marine bioapatites. The treatment was effective and at 8 weeks the defect had remodeled 50.24%. Eighteen months after surgery, the defect had remodelled 94.23% The limp disappeared after surgery and functional recovery was good in all stages after surgery. No adverse reactions were observed at the local or systemic level. This is the first report of a benign bone cyst in an adult female Teckel dog with a lameness, successfully treated with a novel marine bioapatite.